Antimicrobial activity evaluation and phytochemical screening of Bauhinia racemosa L.A possible alternative in the treatment of multidrug-resistant microbes (International Journal of Food and Nutritional Sciences, 2022)
The bark of Bauhinia racemosa are reported to have great medicinal value. The present study was carried out to evaluate the antimicrobial activities and phytochemical evaluation of methanol, ethanolaqueous, acetone and petroleum etherextract of Bauhinia racemosa (Caesalpiniaceae) stem bark. Phytochemical screening of the plant bark reveals the presence of carbohydrates, alkaloids, phenols, steroids and tannins. The methanol, ethanol, aqueous, acetone and petroleum ether extracts of bark of B. racemosa Lamk. prepared and antimicrobial activity were studied by agar well diffusion method against enteric bacterial pathogens such as E. coli, S. aureus, B. subtilis, P. aeruginosa and fungi A. niger and C.albicans. The methanol extracts showed broad-spectrum antimicrobial activity against all tested microorganisms. The results obtained in the present study indicate thatBauhinia racemosa can be a potential source of natural antimicrobial agents.